Efektivitas Penggunaan Word Category Terhadap Peningkatan Minat Belajar Kosakata Pada Mata Pelajaran Bahasa Inggris - Terasne, Terasne; Permana, Dira; Setianingsih, Tri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
The purpose of this study was to determine whether the use of Word Category was effective in increasing the interest and learning achievement of students' vocabulary in English subjects at SMPN 1 Praya Barat. This research was a pre-experimental research with one-group pre-test-post-test design. The population of this research was all students of class II of SMPN 1 Praya Barat which were divided into 3 classes. They were class II-1 consisting of 23 students, class II-2 consisted of 32 students, and class II-3 consisted of 20 students. The total population of this study was 74 students. In this case, researchers took one class as a sample that was class II-1 consisting of 23 students. The research sampling technique used cluster random sampling classes. The research instrument used in the collection of research data was a multiple choice test to measure student vocabulary learning outcomes consisting of 25 items with various variants of questions and questionnaires with an alternative scale of answer choices to measure student vocabulary interest. The results found that the answers: strongly agree given a score of 5, agree given a score of 4, a score given doubtful 3, disagree score given 2, and strongly disagree given a score in this case the questionnaire research as the main data using the description method involving description and data interpretation. Researchers use questionnaires to determine student motivation in reading. Results of the analysis of the data description of the scores of the mean pre-test and Post-test deviation of students were obtained by dividing the number of deviation scores by the number of students seen 194/23 = 8,435. In this study, the sample of data was 23 students, so the level of freedom (df) used was 23-1 = 22. After calculating the data interpretation it was found that t-test = 9,467 ≥ t-table = 1,717. From the above results, the researcher concludes that the word category technique has a significant effect on students' reading comprehension. Therefore, the Alternative Hypothesis was accepted and the Null Hypothesis was rejected